Assessing the Explanatory Power of Social Movement Theories across the Life Course of the Civil Rights Movement. (October 2019) - Maher, Thomas V.; Martin, Andrew; McCarthy, John D.; Moorhead, Lisa
Social movements are constantly evolving. Protest activity waxes and wanes as movements suffer through prolonged periods of frustration, win occasional gains, and turn to new goals and issues. While theoretical models of protest activity are often sensitive to this reality, empirical models typically treat these explanations as time-invariant, rather than situated in specific moments in movements' histories. Quite simply, we suspect that the effect of important predictors of movement activity, notably access to resources, political opportunities, repression, and competition, varies depending on the specific moment in the movement's life course. We explore this possibility through a detailed analysis of three main periods of the American Civil Rights movement: (1) the movement's initial success (1960–1968), its subsequent demobilization (1968–1977), and its institutionalization (1978–1995). Our analysis builds on limited work arguing for greater sensitivity to a movement's life course when explaining protest activity. We find that the type of organizational resources that shape mobilization varies across periods, and support for prior work showing that the concurrent push and pull of institutionalization and radicalization led to demobilization. Finally, we find that coalition work motivated protest during its period of institutionalization. We conclude by discussing the theoretical and empirical implications of these findings.